Extra-pelvic endometriosis presenting as recurrent hepatic cyst: case report and literature review - Mushtaq, Ruqia; Ameer, Aqsa; Hanif, Muhammad; Rauf, Fatima (International Surgery Journal, 2021)
Hepatic endometriosis is a very rare form of endometriosis first described by Rokitansky in 1986. To our knowledge, 42 cases of hepatic endometriosis have been reported in the literature till date. The condition offers a diagnostic challenge owing to its variable presentation on imaging and the need for histological and immunohistochemical evidence for a definite diagnosis. We hereby present the 43rd case of ectopic endometrium in the liver of a 30 years old, multiparous female who presented with fever and pain in the right hypochondrium. Radiological imaging suggested a cystic lesion which was managed laparoscopically. Histopathology and immunohistochemistry findings came out to be consistent with endometriosis. The case highlighted the importance of considering endometriosis as a differential in all women irrespective of age and previous history of endometriosis.